Handbook of Gynecology - Shoupe, Donna (Springer International Publishing : Imprint: Springer, 2017)
Covering all aspects of gynecology commonly encountered in day-to-day practice, this exhaustive work provides a practical, one-stop reference work for clinicians working in the field. This carefully-designed volume includes ten sections, beginning with comprehensive coverage of office-based gynecology, and continuing on to present disease processes and management information by patient age group. Each chapter includes background information, current recommendations for screening, diagnostic criteria, common and uncommon associated problems, approach to diagnosis, summary of treatment options, and an overview of ICD-9/10 codes for specific diagnoses. The handbook concludes with an easy-to-navigate presentation of minimally-invasive operations, surgical procedures, neoplasms, and pathology. Advantages and risks associated with management of particular diseases are covered, along with multiple tips for avoiding complications. Edited by experts and presenting the most recent developments in gynecological practice, The Handbook of Gynecology is an invaluable reference for OB/GYNs, family medicine and internal medicine clinicians, medical students, residents, physician assistants, nurse practitioners, and other healthcare providers.- Resumé vydavatel
Keywords: gynekologie; reprodukční medicína; gynecology; reproductive medicine; elektronické knihy; příručky; electronic books; handbooks and manuals